Formulasi Granul Effervescent Sari Kering Lidah Buaya sebagai Makanan Tambahan - Muthmaina Wijayati; Nyi Mekar Saptarini; Irma Erika Herawati (Indonesian Journal of Pharmaceutical Science and Technology, 2014)
Aloe vera has high nutrition content, but bitter taste so direct consumption infrequently. The bitter tastes overcome with preparation. The aim of this study is to make effervescent granule of dried aloe gel as food supplement. The steps in this study consist of making of dried aloe gel, phytochemistry screening and formulation of effervescent granule, quality tests, and hedonic test of effervescent granule. Freeze drying produced 7.57% dried aloe gel. Phytochemistry screening showed quinones, flavonoids, and saponins content. Effervescent granule formulated with concentration of dried gel 20% (F1), 25% (F2), and 30% (F3). The result of granule quality tests showed that effervescent granule meet good requirements with moisture content 0.20-0.21%, bulk density 0.5341-0.5384 g/mL, tapped density 0.6154-0.6178 g/mL with Carr index 13.29±0.025%, flow rate 9.61-9.71 g/s, rest angel 27.15-27.79o, pH 5.82-5.8, and F1 as the most favorable formula. Keywords: Aloe vera, dried gel, effervescent granule, food supplement